If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -8) = (16) Reorder the terms: (-8 + 3x) = (16) Remove parenthesis around (-8 + 3x) -8 + 3x = (16) -8 + 3x = 16 Solving -8 + 3x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 3x = 16 + 8 Combine like terms: -8 + 8 = 0 0 + 3x = 16 + 8 3x = 16 + 8 Combine like terms: 16 + 8 = 24 3x = 24 Divide each side by '3'. x = 8 Simplifying x = 8
| (5x+10)=(6x-1) | | x-8/x2 | | x-5/x4 | | 0.19x-3.3=0.57x+0.17 | | 4/12=v/9 | | F(x)=4x^2-9x-7 | | (3/2x^(1/2))-3x=0 | | 3x-4+(9-5)=3x(4-2)+5 | | -2e^2x=-44 | | (3/2x^1/2)-3x=0 | | 10p+24=38 | | 3/2x^1/2-3x=0 | | 5cosx=6.5-12sinx | | y=250x+.10 | | 4/√3 | | F=on | | (a/-4)=1 | | 32+(-14)= | | 3x-10(x+2)=169-7x | | A/3-5=12 | | 14x+28=4 | | 2a+3c-a-c= | | 6(2x-3)-3x=5x+8 | | 9x^2+4y^2-8y-32=0 | | 5x=-3.7 | | 7x-5=27 | | 9y=5y+5-9 | | An+c=5 | | b/8=9/5 | | 7x-2=7-17 | | 3l+6=p | | 2(y-5)-5=3 |